Accepting Leadership Responsibility: Preparing Yourself to Lead Honestly, Humanely, and Effectively. Issue 3 (July 2017) - McConnell, Charles R.
Abstract : Many who enter management are ready and willing to accept the benefits of their positions, but not all are readily accepting the full responsibilities of leadership. All too frequently, modern leadership seems self-serving, with the needs and desires of the leaders taking precedence over the needs of the followers and even the needs of the clients or customers. True leadership, however, should primarily benefit the followers rather than the leader. Leaders lead and followers follow for essentially the same reason—fulfillment of needs—so leaders and followers are fundamentally little different from each other. Every manager at every level has organizational superiors, so every leader is a follower as well. A true leader among managers is one who subordinates personal needs to the organization's needs, places employees well above self in importance, models appropriate behavior for employees, and functions as a facilitator in the employees' continuing efforts to get the necessary work done efficiently and effectively.